Upaya Meningkatkan Hasil Belajar Mahasiswa Pada Matakuliah Fisika Modern Melalui Pendekatan Konstruktivisme Model Pembelajaran Kooperatif Tipe Jigsaw - Hadi, Arif Ismul; Samdara, Rida (Lambung Mangkurat University Press, 2009)
The purpose of this research is increase of to study result in ModernPhysics course with constructivism approaching of cooperative model jigsawtype. The results show that application of cooperative model jigsaw type can beincreasing to study result with average value added percent is 2.57% (67.61-69.35) and study comprehensiveness is 37.64% (58.1%-70.79%), studentactivity in Modern Physics education involving lectures increase in good category(28.5 average). The topics in the matter can be increasing to absorb power ofstudent.